EPIBIONTS ASSOCIATED TO MARINE LITTER IN BEACHES FROM URUGUAY, POSSIBLE INDICATORS OF ITS ORIGIN (Boletín de la Sociedad Zoológica del Uruguay, 2025)
Marine anthropogenic litter has been recognized as a serious environmental, economic, human health, and aesthetic problem worldwide. Sandy beaches provide numerous ecosystem services in addition to recreation and are highly affected by marine litter. This study evaluated the composition of marine litter on three oceanic beaches from Uruguay, assessing buoyancy and the presence/ absence of epibionts growing on it. Floating plastics without epibionts were the most abundant type of litter in all the studied beaches. The absence of epibionts on litter allowed us to infer that sources of litter were mainly local. Additionally, a small proportion of floating plastics presenting epibionts (bivalve, bryozoans and barnacles) was registered, evidencing that those remained in the ocean time enough to be colonized before washing up on the beach, probably boosted by ocean currents. Our results suggest that most litter on these beaches has a local origin. This might be a consequence of poor management of waste generated by human activities in the region. Consequently, recommendations are to approach the problem from a local perspective including management and environmental education of communities.
Keywords: marine litter; plastics; sandy beach; epibionts